Peri-urbanization and differentiation in the urban soil market in Carabayllo - Pimentel Sánchez, Nekson (2018)
Carabayllo, district of North Lima, in the last decades, has experienced a substantial loss of periurban agricultural land due to the development of real estate programs, process with repercussions in the lifestyle, social relations, as well as in the forms and mechanisms of possession space.This article, in a synoptic and specific way, and based on data collected in field work, has the purpose of analyzing the processes of periurbanization and differentiation produced by the urban land market in Punchauca, one of the populated centers of Carabayllo.